2019
DOI: 10.1002/iub.2196
|View full text |Cite
|
Sign up to set email alerts
|

P53‐regulated lncRNA uc061hsf.1 inhibits cell proliferation and metastasis in human esophageal squamous cell cancer

Abstract: The expression of long noncoding RNAs (lncRNAs) is closely associated with cancer development and progression, making these lncRNAs potentially novel therapeutic targets. In this study, we aimed to explore the potential function of lncRNA‐uc061hsf.1 in esophageal squamous cell carcinoma (ESCC). The expression of lncRNA‐uc061hsf.1 in ESCC tissues and cell lines was detected by quantitative real‐time polymerase chain reaction (qRT‐PCR). Cell proliferation, apoptosis, and metastasis were detected via CCK‐8, flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…p53 is frequently inactivated or lowly expressed in human cancer, and it is able to directly bind to gene promoters to promote or inhibit gene expression (Vousden and Prives, 2009). Currently, numerous lncRNAs are identified as the targets of p53, such as uc061hsf.1 (Yao et al, 2020), PiHL (Deng et al, 2020), and TRMP (Yang et al, 2018). Herein, two p53 binding motifs on ST8SIA6-AS1 promoter were predicted using in silico analysis, and we performed ChIP and luciferase reporter assays and found that p53 could bind to the motif away from the transcription initiation site, inhibiting ST8SIA6-AS1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…p53 is frequently inactivated or lowly expressed in human cancer, and it is able to directly bind to gene promoters to promote or inhibit gene expression (Vousden and Prives, 2009). Currently, numerous lncRNAs are identified as the targets of p53, such as uc061hsf.1 (Yao et al, 2020), PiHL (Deng et al, 2020), and TRMP (Yang et al, 2018). Herein, two p53 binding motifs on ST8SIA6-AS1 promoter were predicted using in silico analysis, and we performed ChIP and luciferase reporter assays and found that p53 could bind to the motif away from the transcription initiation site, inhibiting ST8SIA6-AS1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, we identified that PKM2, a new target gene of miR-1294, played key roles in miR-1294mediated actions in osteosarcoma cells. Moreover, the tumor-suppressing role of miR-1294 has been reported in other of tumors, such as gastric cancer, 8 esophageal squamous cell carcinoma, 19 epithelial ovarian cancer, 7 oral squamous cell carcinoma, 9 and glioma. 11 Uncontrolled growth, invasion, and metastasis are the main characteristics of tumor cells.…”
Section: Discussionmentioning
confidence: 96%
“…Cell proliferation was determined by CCK-8 assay. 19 In brief, cells were seeded into 96-well plates at 4×10 3 cells per well. After culture for 0, 24, 48, 72, or 96 h at 37°C in 5% CO 2 , the medium was discarded and replaced with 100 μL complete medium and 10 μL CCK-8 (Sigma, St. Louis, MO, USA).…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
“…uc061hsf.1 is a direct transcription target of p53. uc061hsf.1 regulates the expression of the downstream transcription factor FoxA1 and inhibits the proliferation and migration of ESCC cells, indicating that uc061hsf.1 is a tumor suppressor LncRNA regulated by P53 ( 61 ).…”
Section: Long-chain Non-coding Rnas Inhibit the Occurrence And Develo...mentioning
confidence: 99%